Microstructure and mechanical properties of Mg–9Li–3Al–xGd alloys. (July 2015) - Zhang, B.; Peng, X. D.; Ma, Y.; Li, Y. M.; Yu, Y. Q.; Wei, G. B.
Abstract : The influence of gadolinium on the microstructure and mechanical properties of Mg–9Li–3Al alloy was investigated. Results show that the addition of Gd can effectively refine the α-Mg phase and change the morphology of the α-Mg phase. Meanwhile, the Al3 Gd phase is mainly distributed at the boundaries of the α-Mg phase and inside the α-Mg phase. The mechanical property tests reveal that the addition of Gd can effectively improve the mechanical properties of the as cast alloys. When the content of Gd is 2·0%, the tensile strength and yield stress (engineering stress) reach max values of 188 and 174 MPa respectively. When the content of Gd addition is 2·5%, the elongation of the alloy is 15·7%.